Development of SRAP Markers Linked to a Gene for Stem Nematode Resistance in Sweetpotato, Ipomoea batatas (L.) Lam. - Ning ZHAO; Hong ZHAI; Xiao-xia YU; Zhe-sheng LIU; Shao-zhen HE; Qiang LI; Dai-fu MA; Qing-chang LIU (Journal of Integrative Agriculture)
Sequence-related amplification polymorphism (SRAP) markers closely linked to stem nematode resistance gene were developed in sweetpotato, Ipomoea batatas (L.) Lam. Using bulked segregant analysis (BSA), 200 SRAP primer combinations were screened with the resistant and susceptible bulked DNA from the 196 progenies of an F1 single-cross population of resistant parent Xu 781×susceptible parent Xushu 18, 77 of them showed polymorphic bands between resistant and susceptible DNA. Primer combinations detecting polymorphism between the two bulks were used to screen both parents and 10 individuals from each of the bulks. The results showed that primer combination A9B4 produced 3 specific bands in the resistant plants but not in the susceptible plants, suggesting that the markers, named Nsp1, Nsp2 and Nsp3, respectively, linked to a gene for stem nematode resistance. Primer combination A3B6 also produced a SRAP marker named Nsp4 linking to the resistance gene. Amplified analysis of the 196 F1 individuals indicated that the genetic distance between these markers and the resistance gene was 4.7, 4.7, 6.3, and 9.6 cM, respectively.